Visceral leishmaniasis. Kala-azar. Acute kidney injury. Mortality. Risk factors. RIFLE - Michelle Jacintha Cavalcante Oliveira (2010)
Background. There are few studies of renal function evaluation in visceral leishmaniasis (Kala-azar). The aim of this study was to investigate the clinical manifest and the risk factors associated with acute kidney injury (AKI) based on RIFLE criteria in patients with visceral leishmaniasis (VL). Methods. A retrospective study of medical records from patients over 14 years old, without previous kidney disease, with VL, treated at SÃo JosÃ Infectious Diseases Hospital, from 2002 to 2008. Clinical manifestations and risk factors for AKI (defined by using RIFLE criteria) were studied. A multivariate analysis was performed to analyze the risk factors for AKI. Results. A total of 224 patients were included. The mean age was 36Â15 years and 76.8% were males. AKI was observed in 76 patients (33.9% of cases) and % 52.6 (40) were class F on RIFLE criteria. The main clinical symptoms were dyspnea, edema and jaundice in patients with VL and AKI (p<0.05). Oliguria was observed in 6.5% of patients with AKI. Risk factors associated with AKI were male gender (OR=2.2, 95% CI= 1.0-4.7, p=0.03), age > 40 years (OR = 1.05, 95% CI= 1.02-1.08, p < 0.001) and jaundice (OR=2.9, 95% CI= 1.5-5.8 p=0.002). There was an strong association between amphotericin B use and AKI (OR=18.4, 95% CI=7.9-42.8, p<0.0001), whereas glucantimeÂ use was associated with a lower incidence of AKI when compared to amphotericin B users (OR=0.05, 95% CI=0.02-0.12, p<0.0001). Mortality was 13.3% and it was higher in AKI patients (30.2% vs. 4.7%, p<0.0001). RIFLE criteria presented mortality 40%, 20.8% e 35% in R, I and F respective class. Conclusions. The risk factors associated with AKI in patients with VL were male gender, advanced age, jaundice and amphotericin B. The last one was the most important factor of AKI in VL.